2011
DOI: 10.1590/s1808-18512011000100012
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentos de avaliação clínica e funcional em cirurgia da coluna vertebral

Abstract: Alguns dos indivíduos submetidos à cirurgia de coluna vertebral terão desfechos pós-operatório desfavoráveis, independente do êxito técnico. Esse insucesso gera aumento da morbidade e dos custos socioeconômicos. Sabe-se que fatores psicossociais interferem na impressão do sujeito. Com o propósito de identificá-los, tem-se estimulado a busca de preditores prognósticos por meio de instrumentos de triagem. Porém, a eleição do mais adequado pode ser difícil, já que existe um grande número de questionários. Entre o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 69 publications
0
35
0
22
Order By: Relevance
“…22 For the evaluation of the intensity of cervical axial pain, the Visual analog scale (VAS) was used, graded from 0 to 10, where 0 equals the absence of pain and 10 the strongest pain the patient has ever felt. 23 Statistical analysis was performed using STATA 11 SE software. The normality of the variables was tested by the Shapiro-Wilk test and the correlation analysis was tested by calculating the Pearson correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…22 For the evaluation of the intensity of cervical axial pain, the Visual analog scale (VAS) was used, graded from 0 to 10, where 0 equals the absence of pain and 10 the strongest pain the patient has ever felt. 23 Statistical analysis was performed using STATA 11 SE software. The normality of the variables was tested by the Shapiro-Wilk test and the correlation analysis was tested by calculating the Pearson correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22] Large centers and various authors have reported that social and psychological disorders, such as anxiety, depression, hopelessness, sensitivity to stress, sexual disorders, sleep disorders, marital problems, litigation, and worker compensation occur more frequently in patients with spinal problems. 1,3,8,12,[23][24][25][26][27][28] And even more importantly, some of these factors can negatively impact surgical treatment of the spine, depression being a factor frequently studied in the psychological field 23,25 and WC the most often cited factor in the social arena.…”
Section: Discussionmentioning
confidence: 99%
“…O instrumento é recomendado para avaliar a incapacidade funcional associada à dor cervical, sendo de fácil aplicação (21) . Contém 10 itens, cada item composto de 10 questões, entre as quais: sete estão relacionadas às atividades de vida diária, duas relacionadas à dor e uma relacionada à concentração, com ex ceção da questão cinco, sobre cefaleia.…”
Section: Sexounclassified